2013
DOI: 10.1021/mp300650y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Studies of Poly(amidoamine) Dendrimer Based Simvastatin Oral Formulations for the Treatment of Hypercholesterolemia

Abstract: The aim of this investigation was to evaluate the in vivo potential of poly(amidoamine) dendrimers (PAMAM) based simvastatin (SMV) formulations as nanoscale drug delivery units for controlled release action of simvastatin. Drug-dendrimer complexes were prepared and characterized by Fourier transform infrared (FTIR) spectroscopy. In a pharmacodynamic study, the percent increase in cholesterol was less with PAMAM dendrimer formulations as compared to pure drug. The cholesterol level was increased to 20.92% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…These PD profiles suggested that the slow release kinetics of SMV from PEGylated dendrimer-SMV complexes sustained a steady-state SMV concentration in the blood. All these results well align with in vitro release kinetics of SMV from this formulation [5].…”
supporting
confidence: 83%
“…These PD profiles suggested that the slow release kinetics of SMV from PEGylated dendrimer-SMV complexes sustained a steady-state SMV concentration in the blood. All these results well align with in vitro release kinetics of SMV from this formulation [5].…”
supporting
confidence: 83%
“…Enhancement of solubility along with stability and possible permeability of drug owing to the dendrimer helped simvastatin achieve better pharmacokinetic performance compared to the drug alone in animal models (Fig. ) …”
Section: Perspectivementioning
confidence: 99%
“…Plasma concentration of simvastatin released from suspension and drug–dendrimer formulations with amine (DN2), hydroxyl (DO2), and pegylated (DP2) surfaces …”
Section: Perspectivementioning
confidence: 99%
“…Dendrimers have an ideal structure to develop a targeted drug delivery system where drug molecules can be encapsulated in the internal cavities while conjugating a targeting ligand to the free functional groups on the surface. Dendrimers are hyper-branched, nano-sized and multifunctional carrier systems having open internal cavities and free functional groups on their surface 22 23 24 25 26 27 .…”
mentioning
confidence: 99%